Obtención de miel a partir de la Jícama (Smallanthus sonchifolia P&e), Azucarero - Barreros Espín, Johana Abigaíl (2017)
The research was carried out at the University Technical of Cotopaxi, Agroindustrial Engineering Career. The present reseach was focused on the obtaining of honey from the jicama (Smallanthus sonchifolia P&E), "Azucaroso", for this reseach experimental tests with roots of the variety (Smallanthus sonchifolia P&E) were carried out. The experimental work was divided into two sections. The first consists of extracting the juice applying a pressure method by means of an extractor where filtration and clarification were carried out in which the juice was subjected to boiling with a quantity of 50 ml of mucilage obtained from the Yausabara (Pavonia sepium St. Hill). Second, the juice was subjected to concentration by means of the stove for it was worked with temperatures above 100 ºC. For the concentration, a completely randomized mathematical model with factorial arrangement AxB (22) with two replicates was used, having 2 study factors with high and low levels (15 hours - 13 hours and 110ºC - 113ºC). The response variables that were obtained through the sensory evaluation were: color; Light coffee, flavor; sweet scent; Moderate characteristic and consistency: liquid viscous. Statistical analyzes were performed using the INFOSTAT software, with the best treatment result being the t1 treatment, which corresponds to 15 hours at 110 ° C, the amount exposed to concentration was 400ml, resulting in 20ml of honey. The physical-chemical and microbiological analyzes were carried out in the Quìmicalabs laboratory, obtaining as a result 82ºBrix, pH 6.12, fructose 18.76, glucose 34.95 same that is in the ranges established by the Cuban Standard 371 (National Bureau of Normalization, 2012). The results of the microbiological analyzes were; 1.2 x 103 CFU / 10g of mesophilic aerobic colonies, in terms of molds and yeasts present in the sample, were <10 CFU / 10g ensuring that the processed product is under hygiene and quality standards according to the parameters established by the Salvadoran Standard NSO 67.19.01: 08.